Multimedia courseware in the ESL classroom - tool or tutor? - Jangal, Barau (University Malaysia Sarawak, (UNIMAS), 2005)
With the increasing power and sophistication of modern technology, Multimedia Courseware plays a vital role in the field of education. Many research have been carried out on the potential of Multimedia Courseware found out that it is a powerful educational tool to support and facilitate teaching. Even though the potential of the Multimedia Courseware are well documented but how it is actually used in the ESL classroom have not been investigated. The objective of this study is to investigate the use of Multimedia Courseware among ESL teachers in Lower Secondary School in the teaching of Language Skills. Apart from that, this study also intends to find out the factors that contribute to the use of Multimedia Courseware among ESL teachers in Lower Secondary School in the teaching of Language Skills. This study was carried out using questionnaire and interview to 18 ESL teachers in 3 schools in one district in Kuching. The result of this study indicates that there is a high degree of tendency among ESL teachers in Lower Secondary School uses the Multimedia Courseware as tutor to teach Listening Skill, Speaking Skill and Writing Skill. However, they use it as tool to teach Reading Skill. The content of the courseware appears exactly as in the textbook, thus, without hesitation they just projected the courseware onto the screen. Lack of special training in Multimedia application is another reason. A specific approach must be taught in training, courses or workshops to acquire experiences, exposure and knowledge in order to utilize the potential of the Multimedia Courseware to the maximum.